Accounting for the stateless; In search of the Republic of Vietnam war dead - Alex Thái Đình Võ (Human Remains and Violence)
Finding, identifying and interring the war dead are ethically and ceremonially crucial tasks for healing, repairing and legitimising. Before the end of the Vietnam War, the United States had begun to look for missing Americans in Vietnam, Laos and Cambodia. In the wake of its victory and takeover of South Vietnam, the Socialist Republic of Vietnam went to great lengths to identify and immortalise its fallen soldiers. The same cannot be said for the war dead of the Republic of Vietnam, whose fall on 30 April 1975 made the war dead stateless; consequently they have never been legitimately acknowledged by the current Vietnamese government or their former ally, the United States. This article explores the accounting efforts by Nguy ̃ên –Da. c Thành and the Vietnamese American Foundation to reveal the financial, logistical, technical and political opportunities and challenges in accounting for war dead associated with a state that no longer exists.